2016
DOI: 10.1038/srep26297
|View full text |Cite
|
Sign up to set email alerts
|

In actio optophysiological analyses reveal functional diversification of dopaminergic neurons in the nematode C. elegans

Abstract: Many neuronal groups such as dopamine-releasing (dopaminergic) neurons are functionally divergent, although the details of such divergence are not well understood. Dopamine in the nematode Caenorhabditis elegans modulates various neural functions and is released from four left-right pairs of neurons. The terminal identities of these dopaminergic neurons are regulated by the same genetic program, and previous studies have suggested that they are functionally redundant. In this study, however, we show functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…We integrated the OSB system, an auto-tracking microscope system for calcium imaging and optogenetic analyses of neuronal activity in C. elegans (Video 2), with an odor-delivery sub-system (Busch et al, 2012; Tanimoto et al, 2016). Using this new OSB2 system, a moving C. elegans was continuously exposed to an odor flowing from syringe pumps (Figure 3A and Figure 3—figure supplement 1A, and Video 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We integrated the OSB system, an auto-tracking microscope system for calcium imaging and optogenetic analyses of neuronal activity in C. elegans (Video 2), with an odor-delivery sub-system (Busch et al, 2012; Tanimoto et al, 2016). Using this new OSB2 system, a moving C. elegans was continuously exposed to an odor flowing from syringe pumps (Figure 3A and Figure 3—figure supplement 1A, and Video 3).…”
Section: Resultsmentioning
confidence: 99%
“…For the OOSaCaBeN ( O lfactory and O ptogenetic S timulation a ssociated with Ca lcium imaging on Be having N ematode, or OSB2) system, we integrated an auto-tracking microscope system for calcium imaging and optogenetic manipulation with an odor-delivery subsystem (Busch et al, 2012; Tanimoto et al, 2016). Briefly, a wild-type C. elegans (N2) on a NGM plate was placed on a motorized stage HV-STU02 (HawkVision, Japan) combined with an upright microscope and illuminated with infrared light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we analyzed the velocity changes Animals have dramatically lower egg-laying rates when they are removed from their food source. Because dopamine signaling is thought to be elevated in the presence of food (Sawin et al, 2000;Tanimoto et al, 2016), we asked whether increasing dopaminergic neuron activity in the absence of food was sufficient to increase egg-laying rates. Strikingly, we found that activation of dat-1::CoChR could drive animals to lay eggs in the absence of food at significantly higher rates (Figure 4E-F; velocity in Figure 4figure supplement 1B).…”
Section: Acute Changes In Dopaminergic Neuron Activity Control State-mentioning
confidence: 99%
“…Dopamine is responsible for a spectrum of behaviours. It has been shown that it is responsible for slowing of locomotion on the encounter of food [42][43][44][45][46][47] , in local search behaviour along with serotonin 43 , and in learning and decision making [48][49][50] . Dopaminergic neurons are known to be mechanosensory 20,28,42,43,[51][52][53] that have been shown to respond to harsh touch stimulation [54][55][56] with ADE responsible for anterior touch sensation and PDE responsible for its posterior counterparts [57][58][59] .…”
Section: Introductionmentioning
confidence: 99%